2011
DOI: 10.1071/fp11026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global host gene expression during the primary phase of the Arabidopsis thaliana–Plasmodiophora brassicae interaction

Abstract: Abstract. Microarray analysis was used to investigate changes in host gene expression during the primary stages of the interaction between the susceptible plant Arabidopsis thaliana (L.) Heynh ecotype Col-0 and the biotrophic pathogen Plasmodiophora brassicae Woronin. Analyses were conducted at 4, 7 and 10 days after inoculation (DAI) and revealed significant induction or suppression of a relatively low number of genes in a range of functional categories. At 4 DAI, there was induced expression of several genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
86
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 76 publications
(119 reference statements)
8
86
1
Order By: Relevance
“…For example, Ando et al (2005) found that the expression of IPT genes in Chinese cabbage fell 20 DPI in regions of the root system where gall formation was initiated (but was upregulated in areas where galls had yet to form). Likewise Agarwal et al (2011) found that the expression of CK biosynthetic genes was down-regulated 4, 7 and 10 DPI in Arabidopsis -they also found that although the expression of CK glycosylation genes was downregulated at 4 and 7 DPI, expression increased at 10 DPI consistent with our observations at 16 DPI. Siemens et al (2006) performed a microarray analysis of gene expression in control and infected Arabidopsis root and hypocotyl tissue at 10 and 23 DPI.…”
Section: The Regulation Of Host Ck Metabolism and Response In Developsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, Ando et al (2005) found that the expression of IPT genes in Chinese cabbage fell 20 DPI in regions of the root system where gall formation was initiated (but was upregulated in areas where galls had yet to form). Likewise Agarwal et al (2011) found that the expression of CK biosynthetic genes was down-regulated 4, 7 and 10 DPI in Arabidopsis -they also found that although the expression of CK glycosylation genes was downregulated at 4 and 7 DPI, expression increased at 10 DPI consistent with our observations at 16 DPI. Siemens et al (2006) performed a microarray analysis of gene expression in control and infected Arabidopsis root and hypocotyl tissue at 10 and 23 DPI.…”
Section: The Regulation Of Host Ck Metabolism and Response In Developsupporting
confidence: 81%
“…Previous studies using microarray analysis of host gene expression have been crucial in developing our understanding of this plant-pathogen interaction (Siemens et al 2006;Agarwal et al 2011;Schuller et al 2014) but RNASeq provides greater coverage of host gene expression and greater sensitivity at very high or low expression. The recent completion of the P. brassicae genome (Schwelm et al 2015 and studies in our laboratories) also allows the transcriptional response of both the host and pathogen to be studied simultaneously.…”
mentioning
confidence: 99%
“…This molecule plays a central role in the detoxification of reactive oxygen species (ROS) through the GSH-ascorbate cycle, and reacts directly with peroxides in a reaction which is catalyzed by GSH S-transferase (GST) (Noctor and Foyer 1998;Noctor et al 2011). Indeed, transcriptomic and proteomic changes in clubroot-susceptible Arabidopsis (Agarwal et al 2011;) and B. napus (Cao et al 2008) were associated with a significantly higher abundance of transcripts and proteins involved in ROS detoxification and, among them, GST. Modifications of the redox signaling observed during the interaction could be linked to plant basal defense mechanisms.…”
Section: Do Higher Gsh Contents Play a Favorable Role In Plant Or Patmentioning
confidence: 95%
“…Deckers (2006), who focused on changes in the protein compositions in A. thaliana , showed that proteins involved in metabolism, cell defense, cell differentiation, and detoxification were differentially regulated during the initial infection stage. Several studies have addressed the roles of genes related to metabolism, hormone signaling, and defense responses based on transcriptome analyses in specific developmental stages (Siemens et al, 2006; Jubault et al, 2008a; Ludwig-Müller et al, 2009; Agarwal et al, 2011; Schuller et al, 2014). …”
Section: Introductionmentioning
confidence: 99%